The length of the dry season may be associated with leaf scleromorphism in cerrado plants - Souza, Marcelo C. [UNESP]; Franco, Augusto C.; Haridasan, Mundayatan; Rossatto, Davi R. [UNESP]; Araújo, JanaÍna F. de; Morellato, Leonor P. C. [UNESP]; Habermann, Gustavo [UNESP] (Academia Brasileira de Ciências, 2015)
Despite limitations of low fertility and high acidity of the soils, the cerrado flora is the richest amongst savannas. Many cerrado woody species show sclerophyllous leaves, which might be related to the availability of water and nutrients in the soil. To better understand the function and structure of cerrado vegetation within its own variations, we compared two cerrado communities: one in its core region in central Brazil (Brasília, DF) and the other on its southern periphery (Itirapina, SP). We contrasted the length of the dry season, soil fertility rates, leaf concentrations of N, P, K, Ca and Mg and the specific leaf area (SLA) between these communities. The dry season was shorter on the periphery, where the soil was more fertile although more acidic. Plants from the periphery showed higher SLA and higher leaf concentrations of N, P, Ca and Mg. We propose that the higher SLA of plants from the periphery is related to the shorter dry season, which allows better conditions for nutrient uptake.

Apesar das limitações nutricionais e elevada acidez dos solos, a flora do cerrado é a mais rica entre as savanas. Muitas espécies lenhosas do cerrado possuem folhas escleromórficas e o nível de escleromorfismo foliar parece depender da disponibilidade de água e nutrientes no solo. Visando um melhor entendimento sobre a estrutura e funcionalidade da vegetação do cerrado, foram comparadas duas comunidades de cerrado sensu stricto: uma na região central do Brasil (Brasília, DF) e a outra na periferia sul (Itirapina, SP). Para tal, comparamos a duração da estação seca, a fertilidade do solo, as concentrações foliares de N, P, K, Ca e Mg e a área foliar específica (AFE) entre as duas comunidades do cerrado. A estação seca na periferia foi menor em relação à região central, e seu solo foi considerado mais fértil e mais ácido. A vegetação periférica apresentou maior AFE e apresentou maiores concentrações foliares de N, P, Ca e Mg. Baseado nestes resultados, propomos que a maior AFE observada na comunidade periférica se deve à menor duração da estação seca, a qual possibilita melhores condições para absorção de nutrientes do solo.
Keywords: Savanna; Mineral nutrition; Rainfall seasonality; Specific leaf area; Savana; Nutrição mineral; Precipitação; Área foliar específica